The expression is equivalent to [tex]\sqrt[6]{2}[/tex].
Expression; [tex]\dfrac{\sqrt{2}}{\sqrt[3]{2} }[/tex]
The equivalent expression to the given expression.
To determine the equivalent relation following all the steps given below.
Expression; [tex]\dfrac{\sqrt{2}}{\sqrt[3]{2} }[/tex]
The equivalent expression is;
[tex]= \dfrac{\sqrt{2}}{\sqrt[3]{2} }\\\\= \dfrac{2^{\frac{1}{2}}}{2^{\frac{1}{3}}}\\\\ = 2^{\frac{1}{2}-\frac{1}{3}}\\\\ = 2 ^{\frac{3-2}{6}}\\\\= 2^{\frac{1}{6}}\\\\= \sqrt[6]{2}[/tex]
Hence, the expression is equivalent to [tex]\sqrt[6]{2}[/tex].
To know more about Expression click the link given below.
https://brainly.com/question/16450385